EFEK INHALASI AROMATERAPI LEMON, JAHE DAN KOMBINASI TERHADAP FREKUENSI MUAL MUNTAH PADA IBU HAMIL TRIMESTER I - Tamar, Miskiyah; Nursanti, Irna; Nugroho, Natsir (Journal of Islamic Nursing, 2020)
The pregnancy period in a woman's body experiences many changes or adaptations due to fetal growth needs. Various adaptations during pregnancy are adaptations of physiology to the digestive system, endocrine system and adaptations of psychology. Nausea vomiting are normal in pregnancy which occurs around 50-90 % of pregnant women experience nausea in the first trimester. Nausea vomiting in pregnant women will be better if it is able to overcome the problem of nausea in early pregnancy by using non-pharmacological supplementary therapy. Nonpharmacological therapy is non-instructive, non-invasive, inexpensive, simple, effective, and without adverse side effects. Non-pharmacological therapy can be done by giving aromatherapy. The purpose of this study is to prove the comparison between the lemon, ginger and combination aromatherapy inhalation intervention to decrease nausea and vomiting in pregnant women in the first trimester. The design of this study used Quasi Experiment Pre-Post Test Design. The number of research samples for each group is 10 respondents.The purposive sampling research technique.The measuring instrument used a standard questionnaireRhodes INVR.Data analysis using Wilcoxon test and Kruskal Wallis test. The results showed that there were differences in the Mean rank before and after aromatherapy lemon inhalation interventions, inhalation of ginger aromatherapy, and combination against the frequency of nausea vomiting in pregnant women in the first trimester. The highest pre-post mean rank is the combination of aromatherapy inhalation interventions is 17,60 and post 18.20. It can be concluded that combination intervention is more effective in reducing nausea and vomiting in first trimester pregnant women.Keywords: Lemon aromatherapy, Ginger aromatherapy, Nausea vomitingin first Trimester